Colostomy Takedown: Ischemic Complication following Anorectal Malformation Surgery - Wendy Jo Svetanoff; Justin Sobrino; Grace S. Mitchell; Rebecca M. Rentea (Case Reports in Surgery)
Introduction. Anorectal malformations (ARM) are complex disorders that often require staged reconstructions. We present a case and imaging findings of a child who developed issues following colostomy closure due to segmental colonic ischemia. Case Presentation. A 3-year-old female with Currarino syndrome presented with abdominal distention, blood-flecked stools, and prolonged cecostomy flush time. For her anorectal malformation, a colostomy was initially placed. A new colostomy was created at posterior sagittal anorectoplasty (PSARP) to allow the distal rectum to reach the anus without tension. Differentials for her presenting symptoms included a mislocation of the anus, stenosis at the anoplasty site, stricture within the colon, or sacral mass from Currarino syndrome, causing obstructive symptoms. Workup at our hospital included an anorectal exam under anesthesia (EUA), which showed a well-located anus with without stenosis at the anoplasty site, and an antegrade contrast study revealed a featureless descending colon with a 3-4 mm stricture in the distal transverse colon at the site of the previous colostomy, without an obstructing presacral mass. To alleviate this obstruction, the child underwent removal of the chronically ischemic descending colon and a redo-PSARP, where the distal transverse colon was brought down to the anus. She is now able to successfully perform antegrade flushes. Conclusion. Patients who have had prior surgeries for ARM repair are at a higher risk of complications, including strictures or ischemic complications at areas of previous surgery or colostomy placement. A thorough preoperative workup, including contrast studies, can alert the surgeon to these potential pitfalls.